2023
DOI: 10.17533/udea.ikala.v28n1a08
|View full text |Cite
|
Sign up to set email alerts
|

Interactional Metadiscourse Markers in English Research Article Abstracts Written by Non-Native Authors: A Corpus-Based Contrastive Study

Abstract: Abstracts in research articles play a crucial role in settling the impact of academic articles. However, despite the abundance of research on academic discourse, variation in its linguistic features among scholars from different academic cultures seems to have remained untouched. This corpus linguistics study presents a comparative analysis of interactional metadiscourse markers in 96 research article abstracts written in English by both Russian and Spanish scholars in the field of linguistics. The study is ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The findings align with the previous literature in that hedges are the most frequent type of MDMs. This finding is found with Malaysian and Thai academic writers (Hayisama et al, 2019) international students (Alyousef, 2015) Spanish and Russian scholars (Boginskaya, 2023) as well as Arab scholars (Alharbi, 2021;Benraiss & Koumachi, 2023). Furthermore, boosters were also found to be the second most commonly used type of MDM (Hayisama et al, 2019;Musa et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…The findings align with the previous literature in that hedges are the most frequent type of MDMs. This finding is found with Malaysian and Thai academic writers (Hayisama et al, 2019) international students (Alyousef, 2015) Spanish and Russian scholars (Boginskaya, 2023) as well as Arab scholars (Alharbi, 2021;Benraiss & Koumachi, 2023). Furthermore, boosters were also found to be the second most commonly used type of MDM (Hayisama et al, 2019;Musa et al, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…This type of learning is based on fast and effective methods of perception, but operates with a limited number of objects. Implicit learning covers a wider range of objects and their relations that cannot be verbalized, but experience gained can be used in practical actions [8].…”
Section: Literature Review Explicit Vs Implicit Instructionmentioning
confidence: 99%
“…The key role of academic writing in researcher's career has attracted attention of a number of scholars and made them to investigate approaches to help students create coherent academic texts, construct various stances and build effective relations with the target audience. Recent research has demonstrated that the teaching of pragmatics as part of the EAP course is both expedient and desirable [1][2][3][4][5][6][7][8] and enables students to signal communicative intentions effectively and highlight authorial stances. Korotkina, for example, who is considered to be a pioneer in the implementation of EAP into the Russian higher education context, claims that this course aims to develop competencies needed to create academic texts in compliance with the international rhetorical conventions [2].…”
Section: Introductionmentioning
confidence: 99%
“…This has given rise to intensive research into prevailing discursive structures and caused writers with different cultural backgrounds to make pragmatic choices. Whilst the use of metadiscourse patterns in L2 academic writing has been explored from a variety of perspectives (Al-Khasawneh, 2017;Alonso Almeida, 2014;Belyakova, 2017;Boginskaya, 2023;Bondi, 2014;Gessesse, 2016;Hu & Cao, 2011;Ji, 2015;Işık-Taş, 2018;Khajavy et al, 2012;Kozubíková Šandová, 2021;Maamuujav et al, 2021;Perales-Escudero & Swales, 2011;Stotesbury, 2003;Van Bonn & Swales, 2007), little empirical research appears to have been carried out on metadiscourse in academic texts by culturally varied authors in terms of their rhetorical styles. The comparative analysis presented here aims to shed light on how writers from different cultures who have been exposed to two different rhetorical styles interact with readers and make their claims persuasive or tentative.…”
Section: Introductionmentioning
confidence: 99%